Natural hazards & disasters - Hyndman, Donald W.; Hyndman, David W. (Cengage Learning, 2017)
Natural hazards and disasters, 5th edition brings course concepts to life with interactive learning, study, and exam preparation tools along with up-to-date, market-leading content. Students gain an understanding of the underlying geological processes, explore the impact these processes have on humans and vice versa, and analyze strategies for mitigating the hazards' physical and financial harm.